ON CRITICAL POINTS OF SOME POLYNOMIALS - Aghekyan, G.V.; Sahakyan, K.P. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
One dynamic property of some polynomials is investigated. The statements about traces of critical points of some polynomials are proved. The equations of curves, on which critical points move, are obtained.
Keywords: geometry of polynomials; zeros of polynomials; critical points